Perencanaan Tebal Lapisan Perkerasan Lentur Jalan Raya dengan Menggunakan Metode Analisa Komponen SNI 1932-1989F - Arthono, Andri; Virginia, Adinda Rizki; Rahayu, Diana; Khoirul, Muhammad (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
The location of the Rawa Jitu road, Bone Bawang Regency, Lampung Province, is a collector road of the type 1 lane, 2 directions and has a road width of 11 m consisting of a 7 meter traffic lane and 2 meter right and left shoulders each. In accordance with the road engineering requirements for road sections in the primary network system of the 2020 Minister of Public Works regulations based on the road class where the Rawa Jitu road section is located, including class III roads, road space requirements are needed in order to determine the size limits for each road section to comply with the classification specified. had been planned in advance. At the research location, the Rawa Jitu road section had an average daily traffic of 11,960 passenger cars, 1,300 passenger buses, 500 medium buses, 3,409 medium trucks, 570 large trucks, 20,760 motorbikes. Like road classification, road space requirements have also been regulated in applicable invitation regulations, especially in PP No. 34 of 2006. The road space in question includes road use space (RUMAJA), road property space (RUMIJA) and road monitoring space (RUWASJA). Based on calculations that have been carried out using the SNI 1732-1989F component analysis method with a planned age of 20 and 10 years, the following are layer D plus 5 cm, surface layer 10 cm, top foundation layer 15 cm, bottom foundation layer 20 cm.